Synergistic effects of hip/knee osteoarthritis and comorbidities on mobility and self-care limitations among older adults: Cross-sectional analysis of the Oxford pain, Activity and Lifestyle study. (2nd December 2020) - Nicolson, Philippa JA; Williamson, Esther; Lee, Hopin; Morris, Alana; Garrett, Angela; Sanchez-Santos, Maria T; Lamb, Sarah E
Objective: To estimate synergistic effects of hip/knee osteoarthritis (OA) and comorbidities on mobility or self-care limitations among older adults. Methods: We used baseline, cross-sectional data from the Oxford Pain, Activity and Lifestyle (OPAL) study. Participants were community-dwelling adults aged 65 years or older who completed a postal questionnaire. Participants reported demographic information, hip/knee OA, comorbidities and mobility and self-care limitations. We used modified Poisson regression models to estimate the independent and combined relative risks (RR) of mobility or self-care limitations, the relative excess risk due to interaction (RERI) between hip/knee OA and comorbidities, attributable proportion of the risk due to the interaction and the ratio of the combined effect and the sum of the individual effects, known as the synergy index. Results: Of the 4, 972 participants included, 1, 532 (30.8%) had hip/knee OA, and of them 42.9% reported mobility limitations and 8.4% reported self-care limitations. Synergistic effects impacting self-care limitations were observed between hip/knee OA and anxiety (RR: 3.09, 95% Confidence Interval (CI): 2.00 to 4.78; RERI: 0.93, 95% CI: 0.01 to 1.90), and between hip/knee OA and depressive symptoms (RR: 2.71, 95% CI: 1.75 to 4.20; RERI: 0.58, 95% CI: 0.03 to 1.48). The portion of the total RR attributable to this synergism was 30% and 22% respectively. Conclusions: This study demonstrates that synergism between hip/knee OA and anxiety or depressive symptoms contribute to self-care limitations. These findings highlight the importance of assessing and addressing anxiety or depressive symptoms when managing older adults with hip/knee OA to minimize self-care limitations.